Determination of Oxidation of Methyl Ricinoleates. (18th April 2015) - Wang, Tong; Lee, Show‐ling; da Silva, José André C.; Hammond, Earl; Yao, Linxing
Abstract: Ricinoleate esters have desirable properties as biolubricants, but their oxidative stability has been questioned. To systematically study the stability of ricinoleate ester and its derivative, methyl esters of castor oil were prepared and methyl ricinoleate was isolated by solvent partitioning. Methyl 12‐acetyl ricinoleate was synthesized from the methyl ricinoleate by interesterification with excess methyl acetate and was then purified by solvent partitioning. The rates of oxidation of methyl linoleate, methyl oleate and the two ricinoleate esters were measured by oxidation of lipid dispersed on glass beads under three temperatures (40–80 °C). The relative amounts of the unoxidized methyl esters were determined periodically by gas chromatography, and the peroxide value of the oils was also determined. The oxidation rates were determined as the peroxide value increase rate, as well as the ester disappearance rate, and the stability of the various esters was compared. Overall, methyl ricinoleate was much more oxidatively stable than methyl oleate at mildly elevated temperatures, and the acetylation of the hydroxyl group on the 12th carbon decreased the stability.